Residual harmfulness of a defect after repairing by a composite patch. (February 2015) - Nateche, T.; Hadj Meliani, M.; Khan, Shafique M.A.; Matvienko, Y.G.; Merah, Nesar; Pluvinage, G.
Highlights: The harmfulness of a defect in a CT specimen made in a steel pipe is evaluated after being repaired with a composite patch. The stress field is evaluated by the notch stress intensity factor Kρ and the effective T -stress Tef as constraint parameter. An assessment point of coordinates [ Tef − Kρ ] is reported in the Fracture Toughness–Constraint Diagram (FTCD). On the line from origin O and passing through this assessment point and intercepting the Failure Material Master Curve, one determine a patch repairing index. Abstract: The harmfulness of a defect in a CT specimen made in an API 5L X52 steel pipe is evaluated after being repaired with a composite patch. Due to the fact that the presence of a composite patch improves the fracture resistance but also modifies the constraint, a two-parameter fracture approach is used. More precisely, the stress field at the tip of a notch-like defect repaired by a boron/epoxy bonded composite patch is evaluated by the notch stress intensity factor Kρ and the effective T -stress Tef as constraint parameter. An assessment point of coordinates [ Tef − Kρ ] is reported in the Fracture Toughness–Constraint Diagram␣(FTCD). A line from origin O and passing through this assessment point intercepts the Failure Material Master Curve. This procedure allows us to determine a patch repairing index which is a measure of the residual harmfulness of a crack-like defect after repair. The repair with a composite patch reduces significantly the defect's severity and increases the service life.